Vietnam's infrastructure constraints - Nguyen, Xuan Thanh (United Nations Development Programme in Vietnam (UNDP in Vietnam), 2009)
This policy dialogue paper examines the infrastructure challenges that Viet Nam faces in the energy and transport sectors. The study examines how well strategic infrastructure planning in these two sectors has been able to identify key bottlenecks and priority needs, and led to the formulation of policy interventions aimed at addressing the various constraints that Vietnam faces in these areas.